IMPACT OF THE COVID-19 PANDEMIC ON POULTRY FEED DISTRIBUTION IN LIMA PULUH KOTA DISTRICT, WEST SUMATRA PROVINCE - Widya Satya Nugraha; Tulus Fernando Silitonga; Bunga Putri Febrina; Adli Putra Ermanda; Ruth Dameria Haloho; Irmayanti Irmayanti; Nita Adilla Pratiwi; Agni Ayudha Mahanani (Faculty of Animal and Agricultural Science, Diponegoro University, 2023)
Since the outbreak of the COVID-19 pandemic in Indonesia, on March 31, 2020, the government of the Republic of Indonesia has adopted a new policy known as PSBB (Pembatasan Sosial Berskala Besar) commonly known as